"Not My Bug!" and Other Reasons for Software Bug Report Reassignments - Guo, Philip J.; Zimmermann, Thomas; Nagappan, Nachiappan; Murphy, Brendan; Nagappan, Nachi; Zimmermann, Tom (Proceedings of the ACM Conference on Computer Supported Cooperative Work (CSCW), 2011)
Bug reporting/fixing is an important social part of the soft-ware development process. The bug-fixing process inherently has strong inter-personal dynamics at play, especially in how to find the optimal person to handle a bug report. Bug report reassignments, which are a common part of the bug-fixing process, have rarely been studied. In this paper, we present a large-scale quantitative and qualitative analysis of the bug reassignment process in the Microsoft Windows Vista operating system project. We quantify social interactions in terms of both useful and harmful reassignments. For instance, we found that reassignments are useful to determine the best person to fix a bug, contrary to the popular opinion that reassignments are always harmful. We categorized five primary reasons for reassignments: finding the root cause, determining ownership, poor bug report quality, hard to determine proper fix, and workload balancing. We then use these findings to make recommendations for the design of more socially-aware bug tracking systems that can overcome some of the inefficiencies we observed in our study.